2010
DOI: 10.1002/jcla.20360
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium‐derived factor as a new marker of metabolic syndrome in Caucasian population

Abstract: Authors present that serum pigment epithelium derived factor (PEDF) is an independent marker of metabolic syndrome in Caucasianpopulation. PEDF was measured with new ELISA sandwich test. J. Clin. Lab. Anal. 24:17-19, 2010. (c) 2010 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 6 publications
6
21
1
Order By: Relevance
“…These findings go on line with another study performed by Stejskal et al (21) who concluded that PEDF is correlated with BMI and that PEDF is …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings go on line with another study performed by Stejskal et al (21) who concluded that PEDF is correlated with BMI and that PEDF is …”
Section: Discussionsupporting
confidence: 92%
“…The association of PEDF with MetS and its components has been verified in many previous studies (21) PEDF level was identified as an independent predictor for the development of MetS. (25) .…”
Section: Table1supporting
confidence: 61%
See 2 more Smart Citations
“…22 Increased PEDF levels are correlating with metabolic syndrome, type 2 diabetes, and abdominal fat distribution. 20,21,31 RBP4 was initially described to be associated with the metabolic syndrome. 9 It is well known that RBP4 is predominately produced and secreted from the adipose tissue.…”
Section: Introductionmentioning
confidence: 99%